Emergency Kit: Poems for Strange Times - Shapcott J. Jo; Sweeney M. Matthew (London, Faber and Faber, 2004)
Ewhich gives prominence to poems rather than to the poets who wrote them. It is truly international, bringingSgether poems not just from these islands but from many parts of the English-speaking world. It is the first book to identify a strain in the poetry of the last half-century which is characterise of the 'strange times' we live in - an age when, as the editors note, scientific discovery has encouraged us to 'make free with the boundaries of realism'. It values imagination, surprise, vivid expression, the outlandish and the playful above ideology and sententiousness. An unashamedly exuberant collection, containing work by intentionally respected poets as well as others who will be new to most readers, it is, in short, living proof that poetry in the English language continues to thrive and to matter.